2016
DOI: 10.1002/jcop.21783
|View full text |Cite
|
Sign up to set email alerts
|

When Housing First Lasts: Exploring the Lived Experience of Single‐site Housing First Residents

Abstract: Mortality rates among homeless adults are estimated to be between three to four times higher than in the general population (O'Connell, 2005;Fazel, Geddes, & Kushel, 2014) This work was performed at the University of Washington, Seattle. Natalie Stahl is now a student at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…This example demonstrates how Housing First principles can be applied in a congregate setting. These findings echo the results of the study of a single-site Housing First program by (Stahl et al 2016). Stahl et al (2016) used a grounded theory approach to study the experience of formerly homeless individuals in a single-site Housing First program.…”
Section: Single-site Housing and Fidelity To Housing Firstsupporting
confidence: 67%
See 2 more Smart Citations
“…This example demonstrates how Housing First principles can be applied in a congregate setting. These findings echo the results of the study of a single-site Housing First program by (Stahl et al 2016). Stahl et al (2016) used a grounded theory approach to study the experience of formerly homeless individuals in a single-site Housing First program.…”
Section: Single-site Housing and Fidelity To Housing Firstsupporting
confidence: 67%
“…These findings echo the results of the study of a single-site Housing First program by (Stahl et al 2016). Stahl et al (2016) used a grounded theory approach to study the experience of formerly homeless individuals in a single-site Housing First program. Their findings suggest that the sense of community and stability of single-site Housing First programs may also support housing retention and stability (Stahl et al 2016).…”
Section: Single-site Housing and Fidelity To Housing Firstsupporting
confidence: 67%
See 1 more Smart Citation
“…Even when employment and social connections are not feasible, feeling settled in one's housing has been linked to housing stability. In qualitative research on life changes following permanent supportive housing, participants' descriptions of making housing "feel like home" through personal belongings, the establishment of routines, and increased safety corresponded with an intention to stay in housing (Stahl et al, 2016). The authors concluded that the perception of being "at home" was a key component of recovery related to the experience of housing and reconstructing one's identity.…”
Section: Importance Of Feeling Like "Home"mentioning
confidence: 99%
“…Research has shown that HF is associated with reductions in alcohol‐related harm, publicly funded service utilization, and associated costs for people experiencing chronic homelessness (Clifasefi, Malone, & Collins, ; Collins, Malone et al, ; Larimer et al, ; Mackelprang, Collins, & Clifasefi, ; Stergiopoulos et al, ; Tsemberis & Eisenberg, ; Tsemberis et al, ). Despite these positive outcomes, many HF residents also continue to experience alcohol‐related harm (Collins, Clifasefi et al, ; Stahl, Collins, Clifasefi, & Hagopian, ). HF residents have also indicated they are interested in community‐based, creative, and meaningful activities to promote community cohesiveness and resident‐driven recovery and growth (Clifasefi, Collins, Torres, Grazioli, & Mackelprang, ).…”
Section: Introductionmentioning
confidence: 99%